2007
DOI: 10.1001/archinte.167.22.2443
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Tuberculosis/Human Immunodeficiency Virus Comorbidity, United States, 1993-2004

Abstract: Background: To our knowledge, this is the first assessment of trends in tuberculosis (TB)/human immunodeficiency virus (HIV) comorbidity in the United States based on national TB surveillance data. Methods:We analyzed all incident TB cases reported to the Centers for Disease Control and Prevention national TB surveillance system from all 50 states and the District of Columbia from 1993 through 2004. Trends in TB/HIV cases were examined according to selected demographic and clinical characteristics.Results: Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
48
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 30 publications
5
48
1
Order By: Relevance
“…Previous studies demonstrated predominance in young adults averaging 33 years of age [12,21,25,26]. The results in our study reflect the prolonged survival of HIV patients, since the average age of those with registered cases of AIDS in Brazil between 2002 and 2005 was 35.4.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Previous studies demonstrated predominance in young adults averaging 33 years of age [12,21,25,26]. The results in our study reflect the prolonged survival of HIV patients, since the average age of those with registered cases of AIDS in Brazil between 2002 and 2005 was 35.4.…”
Section: Discussionsupporting
confidence: 75%
“…There is a much greater risk of HIV/TB co-infected patients developing active TB, either from the latent infection being reactivated or due to the rapid progression of a new infection [10][11][12][13]. The risk of developing active TB in HIV patients increases from 5 to 15% annually, due to the latent infection being reactivated; this depends on the degree of immunocompromise [12,14,15].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1,3,23 Providers who practice risk-based testing might miss HIV infection among female, foreign-born, or older patients, who are increasingly represented among HIV-infected TB patients. 24,25 Although this evaluation detected no or little HIV infection among patients younger than 15 years and patients older than 60 years, infection in these groups does occur. Nationally in 2005, HIV infection was detected in 1% of TB patients younger than 4 years, in 2% of those aged 5 to 14 years, and in 1% of those older than 64 years.…”
Section: Discussionmentioning
confidence: 71%